Respostas

2014-06-04T12:05:09-03:00
X²-x-6=0    equação de 2º grau

0nde a=1  b=-1   c=-6

Δ=b²-4.a.c
Δ=(-1)²-4.1.(-6)
Δ=1+24
Δ=25  ⇒  raiz de 25 é 5



x'=-(-1) + 5      +1+5      6
    ¨¨¨¨¨¨¨¨¨¨¨¨   = ¨¨¨¨¨¨¨¨ =¨¨¨¨¨¨¨=  3
          2.1            2        2


 
x"=(-1) - 5      +1 - 5      -4
    ¨¨¨¨¨¨¨¨¨¨¨¨=  ¨¨¨¨¨¨¨¨¨¨=  ¨¨¨¨¨¨¨= -2                           S:(3, -2)
        2.1            2          2


Bons estudos!


2014-06-04T12:45:48-03:00
X²-x-6=0             a=1 b=1      c=-6                                                                                    b²-4*a*c                                                                                                                     1²-4*1*(-6)                                                                                                                  1+24                                      V25             =            5                                                    -b+V/2*a                                                                                                                     -1+5/2=4/2  2                  x'=2                                                                                      -1-5 /2 = -6/2                    x''=-3